1993
DOI: 10.1182/blood.v81.2.468.468
|View full text |Cite
|
Sign up to set email alerts
|

Subtypes of Epstein-Barr virus (EBV) in Hodgkin's disease: association between B-type EBV and immunocompromise [see comments]

Abstract: Epstein-Barr virus (EBV) has been associated with Hodgkin‧s disease (HD) in up to 50% of cases, but the subtype of EBV involved has only recently been studied. In this report, biopsy samples from 30 patients with HD were assessed for EBV sequences using both the polymerase chain reaction (PCR) and in situ hybridization (ISH). EBV sequences were localized to the malignant Reed-Sternberg cells and their mononuclear variants (Hodgkin's cells) in 9 of the 30 cases, with 7 demonstrating A- type and 2 B-type EBV seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

1994
1994
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(10 citation statements)
references
References 43 publications
2
8
0
Order By: Relevance
“…Moss et al (1988) isolated both CD4 and CD8 cytotoxic T-cell clones that recognize the autologous A-type but not the B-type trans-formed lymphoblastoid cell lines. In HD with an EBV infection, almost all cases were of A-type (Boyle et al, 1993). In our study, all cases except one were of A-type.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Moss et al (1988) isolated both CD4 and CD8 cytotoxic T-cell clones that recognize the autologous A-type but not the B-type trans-formed lymphoblastoid cell lines. In HD with an EBV infection, almost all cases were of A-type (Boyle et al, 1993). In our study, all cases except one were of A-type.…”
Section: Discussionsupporting
confidence: 48%
“…Isolated DNA were used for a polymerase chain reaction (PCR). We synthesized specific primers, to examine the A and B subtypes of the EBV EBNA2 region, on the basis of the published DNA sequence, which corresponded to the Epstein-Barr nuclear antigen (EBNA) 2 region, to detect the A-and B-subtypes of EBV (Boyle et al, 1993). After PCR amplifica-'To whom correspondence and reprint requests should be sent, at the Department of Pathology, School of Medicine, Fukuoka University, Nanakuma 7-45-1, Jonan-ku, Fukuoka 814-01, Japan.…”
Section: Polymerase Chain Reaction (Pcr)mentioning
confidence: 99%
“…Seroprevalence studies have shown that type 2 EBV is unusual in healthy Western populations but relatively frequent in Central Africa and New Guinea. An increased proportion of type 2 positivity has also been reported in patients with HIV infection and in transplant recipients ( Sculley et al , 1990 ; Borisch et al , 1992 ; Boyle et al , 1993 ; De Re et al , 1993 ). By studying the EBNA‐3C gene, we determined that, despite an EBV type 1 prevalence, both in our healthy children and in the paediatric HD population, there was a markedly different distribution of type 2 between the two groups: none of the cases of normal lymphoid tissue contained type 2 EBV and, in contrast, as much as 25% of childhood HD cases harboured it.…”
Section: Discussionmentioning
confidence: 88%
“…It has been proposed that type 2 EBV, which is a less efficient transforming agent than type 1, may require a reduced immunocompetent status to establish widespread infection in vivo and induce the outgrowth of lymphoproliferative disorders ( Boyle et al , 1993). The presence of type 2 EBV in 25 % of children with HD may reflect an impairment of immune function.…”
Section: Discussionmentioning
confidence: 99%
“…15 For EBV subtype, we synthesized primers based on the previous report. 16 The primers (EBNA2 A-5 0 , EBNA2 A-3 0 , EBNA2B-5 0 , EBNA2B-3 0 ) were synthesized. EBV-positive cases were amplified with a second set of primers that immediately flank the polymorphic portion of the EBV LYDMA gene comprising variable numbers of approximately 30 base pairs tandem repeats.…”
Section: O L E C U L a R A Na Lys I Smentioning
confidence: 99%